The Impact Of Clients' Knowledge On Compliance With Anti-Tuberculosis Medication At Home - Jelita Siburian; Rotua Elvina Pakpahan; Vina Ys Sigalingging (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Pulmonary tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis, namely acid-fast bacteria. Successful treatment of patients with tuberculosis (TB) is a problem in today's society. One of the reasons for the increase in pulmonary TB cases is the low level of education of sufferers. One of the causes of failure of tuberculosis treatment therapy is the side effects of anti-tuberculosis drugs (OAT) which can affect the adherence to medication in tuberculosis patients. The success of TB treatment is compliance in taking anti-tuberculosis medication at the prescribed dose. The aim of this research was to determine the relationship between clients' knowledge of pulmonary tuberculosis and compliance with taking anti-pulmonary tuberculosis medication at Harapan Pematang Siantar Hospital. This research was conducted at Harapan Pematangsiantar Hospital in May 2023. This type of research is descriptive quantitative correlational with a cross-sectional approach. Data collection was carried out using a questionnaire with the Gutman scale. The population of this study was all outpatient clinic patients at Harapan Pematang Siantar Hospital in October-December 2022. The sampling technique was accidental sampling, namely 58 respondents who came in May 2023. Statistical test results used the chi square test with a confidence level of 95% (α = 0.05) shows the p value = 0.001, meaning that there is a relationship between the level of knowledge of tuberculosis clients and compliance with taking anti-tuberculosis medication at Harapan Pematang Siantar Hospital in 2023